PENERAPAN LATIHAN RANGE Of MOTION (ROM) PADA PASIEN DENGAN GAGAL GINJAL KRONIK DALAM PEMENUHAN KEBUTUHAN AKTIVITAS - Rahmawati - Said; Fitria - Hasanuddin; Nia Angraini Mokodompit (Media Keperawatan:Politeknik Kesehatan Makassar, 2019)
Chronic kidney failure (CKD) or Chronic Kidney Diseases (CKD) is a problem that occurs in the decline in kidney function because the kidneys become a vital organ in maintaining a healthy body. Decreased kidney function causes the kidneys can not maintain the balance of metabolism, fluid and electrolytes which can lead to uremia. This study aims to see the extent of the application of ROM exercises in Chronic Kidney Failure Patients in Meeting the Needs of Activities. This research is using descriptive case design with a case study approach. The results of this study are intradialysis ROM exercises in patients undergoing hemodialysis therapy can influence the level of fatigue (fatigue). This began to be seen in the treatment of the third to the sixth has changed and the value of fatigue has increased. Which means that the higher the value of fatigue, the better the quality of life of patients with chronic renal failure. But this exercise must be done continuously. Conclusion: Intradilysis ROM exercises in hemodialysis patients can affect the level of fatigue (fatigue).Keywords: Fatigue, ROM Exercise, CKD